Twisted D3-brane and M5-brane compactifications from multi-charge spindles - Boido, A; Perez Ipina, JM; Sparks, J (Springer, 2021)
We construct families of supersymmetric AdS3 × Y7 and AdS3 × Y8 solutions to type IIB string theory and M-theory, respectively. Here Y7 is an S5 fibration over Σ, while Y8 is an S4 fibration over Σg × Σ, where Σg is a Riemann surface of genus g > 1 and Σ is a two-dimensional orbifold known as a spindle. We interpret the solutions as near-horizon limits of N D3-branes wrapped on Σ and N M5-branes wrapped on Σg × Σ, respectively. These are holographically dual to d = 2, (0, 2) SCFTs, and we show that the central charge and superconformal R-symmetry of the gravity solutions agree with dual field theory calculations.